Mendekonstruksi peran pustakawan dalam pemanfaatan kecerdasan buatan di perpustakaan perguruan tinggi - Risky Jumatul Ikhsan; Santoso, Ade Rezeki (Daluang: Journal of Library and Information Science, 2025)
Purpose. This study investigates the deconstruction of the librarian’s role in the application of Artificial Intelligence (AI) at university libraries, specifically at Universitas Negeri Padang (UNP), through Jacques Derrida’s social theory. Librarians are expected to act as key connectors between users and credible information. With the increasing presence of AI in libraries, their role becomes even more critical in enhancing the quality and accessibility of information services. Methodology. This research employs a qualitative approach using the literature study method, with data collection conducted through reference sources, reading, note-taking, and processing research materials Results and discussion. At the UNP Library, the librarian’s role is shifting due to digitalization and AI development. Although facilities like Digilib UNP and SIDARING have been introduced, they are not yet fully optimized. The opening of the new Information and Library Center building provides opportunities for innovation, but a deconstruction of traditional librarian roles is needed. Librarians should not be limited to administrative tasks but encouraged to implement AI-based services such as virtual library tours, chatbots, and speech-to-text systems. Domestic and international case studies confirm that AI integration enhances user engagement and service delivery, requiring librarians to be adaptive, creative, and technologically competent. Conclusions. Applying Derrida’s deconstruction theory, the librarian’s role at UNP must be redefined to meet digital-era demands. Main challenges include resistance to change and lack of technical skills. With a transformative approach, librarians can collaborate and innovate using AI, making library services more inclusive, dynamic, and relevant for modern academic needs.